Substitution across profit shifting methods and the impact on thin capitalization rules - Gideon Goerdt; Wolfgang Eggert (International Tax and Public Finance, 2021)
Thin capitalization rules limit firms' ability to deduct internal interest payments from taxable income, thereby restricting debt shifting activities of multinational firms. Since multinational firms can limit their tax liability in several ways, regulation of debt shifting may have an impact on other profit shifting methods. We therefore provide a model in which a multinational firm can shift profits out of a host country by issuing internal debt from an entity located in a tax haven and by manipulating transfer prices on internal goods and services. The focus of this paper is the analysis of regulatory incentives, (i)[12pt]minimal amsmath wasysym amsfonts amssymb amsbsy mathrsfs upgreek -69pt document(i)document if a multinational firm treats debt shifting and transfer pricing as substitutes or (ii)[12pt]minimal amsmath wasysym amsfonts amssymb amsbsy mathrsfs upgreek -69pt document(ii)document if the methods are not directly connected. The results provide a new aspect for why hybrid thin capitalization rules are used. Our discussion in this paper explains why hybrid rules can result in improvements in welfare if multinational firms treat methods of profit shifting as substitutes.
Keywords: H7; H2; K3; 340; Thin capitalization rules; Profit shifting methods; Substitution